Answer:
p(0) = 35
Explanation:
-3, √7 and 1-√6 are all roots, hence, we can factorize (x-(-3)) = (x+3), (x-√7) and (x- (1-√6)) = (x-1+√6) from p. Since p has rational coefficients, then we need to cancel out both √7 and √6. To do so we should multiply by the rational conjugate, of the expressions (x-1+√6) and (x-√7), that means, where a square root of a non square positive number appears, place the opposing sign there.
The rational conjugate of (x-√7) is (x+√7), and
(x-√7)*(x+√7) = x²-7
On the other hand, the rational conjugate of (x-1+√6) is (x-1-√6), and
(x-1+√6) * (x-1-√6) = ( (x-1) + √6) * ((x-1) -√6) = (x-1)² - √6² = x²-2x+1-6 = x²-2x-5.
Thus, both x²-7 and x²-2x-5 are factors of p. The polynomial has the form
Where c is a constant. To determine c, we need to use the other piece of information given: p(-1) = 8
When we evaluate in -1, we get
Thus, c = 8/24 = 1/3.
Therefore,
I hope that works for you!